2017
DOI: 10.3758/s13414-017-1283-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive basis of individual differences in speech perception, production and representations: The role of domain general attentional switching

Abstract: This study investigated whether individual differences in cognitive functions, attentional abilities in particular, were associated with individual differences in the quality of phonological representations, resulting in variability in speech perception and production. To do so, we took advantage of a tone merging phenomenon in Cantonese, and identified three groups of typically developed speakers who could differentiate the two rising tones (high and low rising) in both perception and production [+Per+Pro], o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…One should also entertain the possibility that executive functions, other than working memory span, might underlay some of the effects noted in our study (Wingfield, 2016). For example, effectiveness of attentional switch was found to correlate with the perception of fundamental speech contrasts (Ou & Law, 2017). In their studies, Ou and Law suggest that the perception of tonal differences in Cantonese were related to scores on an attentional switch task.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One should also entertain the possibility that executive functions, other than working memory span, might underlay some of the effects noted in our study (Wingfield, 2016). For example, effectiveness of attentional switch was found to correlate with the perception of fundamental speech contrasts (Ou & Law, 2017). In their studies, Ou and Law suggest that the perception of tonal differences in Cantonese were related to scores on an attentional switch task.…”
Section: Discussionmentioning
confidence: 71%
“…Although conceptions of working memory differ among theorists (cf. (Baddeley, 2012; Cowan, 1999; Engle, 2002; Oberauer, 2002), there is general agreement that the essence of working memory is represented by individuals’ limited capacity to retain information while manipulating this information in memory or while performing a concurrent task (cf. Baddeley & Hitch, 1974; McCabe, Roediger, III., McDaniel, Balota, & Hambrick, 2010; Postle, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Looked at from another perspective, bilingual speakers do seem to profit from a cognitive processing benefit, evident from generally lower switch costs in a Simon Test and faster RTs in tasks with high working memory demands (Bialystok et al, 2004). The impact of differing attention skills in L2 and bilingual contexts was also studied for VOT productions (Lev-Ari and Peperkamp, 2013), the perception and production of vowels and consonants (Darcy et al, 2016;Safronova, 2016), and tone perception and production (Ou et al, 2015;Ou and Law, 2017). The effects of poorer attention (switching or inhibitory) control bearing on speech processing have been also previously documented in elderly listeners, leading to stronger perceptual learning effects Scharenborg et al, 2015).…”
Section: Individual Cognitive Differences and Phonological/phonetic Pmentioning
confidence: 99%
“…E-Skala provides a general measure (E-Skala General) and two subscales: the E-Skala Social (reflecting "social concern") and the E-Skala Empathy (reflecting "readiness for empathy"). As far as cognitive abilities are concerned, tests of phonological working memory (Gathercole et al, 1994) were also carried out, as it has repeatedly been argued that "phonological short term memory" can predict success in L2 as well as L1 learning and phonological processing (e.g., Baddeley, 2003;Ou et al, 2015;Ou and Law, 2017;Serafini, 2017). For the current study measures for subjects' digit span forward, digit span backward and non-word repetition span were gathered.…”
Section: Psychological and Cognitive Aspectsmentioning
confidence: 99%
“…There is some evidence that tone merger in Hong Kong Cantonese can be partially explained by non-linguistic factors [12,24]. For instance, Ou and colleagues [12] found that visual working memory (as assessed by Coding and Cancellation of WAIS-IV) and auditory attentional switching ability (as assessed by Elevator Counting with Reversal in the Test of Everyday Attention) significantly explained the overall response latencies of tone discrimination in non-merging and merging individuals.…”
Section: Tone Merger In Hong Kong Cantonesementioning
confidence: 99%